1989
DOI: 10.1161/01.str.20.9.1279
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance and clinical cerebrovascular disease. An update.

Abstract: -8 of living systems were reported in the literature. Since that time the clinical application of NMR has experienced exponential growth. Because of this rapid pace of development and the concurrent increase in hospitalbased NMR facilities, it is timely to review the application of NMR to the diagnosis and investigation of cerebrovascular disease.Nuclear Magnetic Resonance Detailed physics of the NMR experiment are beyond the scope of this review. However, the parameters used to determine contrast in magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…MRI has a high sensitivity to detect even small amounts of blood, and blood degradation products are visible for a long time, which makes repeated examinations unnecessary. 5 We performed MRI 3 weeks after the stroke because most hemorrhages occur during this time, as former CT studies have shown. To avoid a selection bias, the patients were consecutive victims of acute TIA or ischemic stroke who underwent a standardized diagnostic routine.…”
Section: Discussionmentioning
confidence: 99%
“…MRI has a high sensitivity to detect even small amounts of blood, and blood degradation products are visible for a long time, which makes repeated examinations unnecessary. 5 We performed MRI 3 weeks after the stroke because most hemorrhages occur during this time, as former CT studies have shown. To avoid a selection bias, the patients were consecutive victims of acute TIA or ischemic stroke who underwent a standardized diagnostic routine.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) (previously nuclear magnetic resonance or NMR) detects the changes of cerebral ischaemia earlier (at less than 4 h) and with greater sensitivity than CT scanning, and smaller infarcts including lacunar strokes are more frequently visualised (Brown et al, 1988;Ramadan et al, 1989) (Table 1, Figure 3). An additional area of superiority of MRI over CT is the differentiation of infarct from oedema, which is important in assessing the effects of drugs such as thrombolytics which may encourage oedema formation while improving cerebral perfusion.…”
Section: Magnetic Resonance Imaging Spectroscopy and Angiographymentioning
confidence: 99%
“…Magnetic resonance imaging, spectroscopy, and angiography Magnetic resonance imaging (MRI) (previously nuclear magnetic resonance or NMR) detects the changes of cerebral ischaemia earlier (at less than 4 h) and with greater sensitivity than CT scanning, and smaller infarcts including lacunar strokes are more frequently visualised (Brown et al, 1988;Ramadan et al, 1989) (Table 1, Figure 3). An additional area of superiority of MRI over CT is the differentiation of infarct from oedema, which is important in assessing the effects of drugs such as thrombolytics which may encourage oedema formation while improving cerebral perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…An additional area of superiority of MRI over CT is the differentiation of infarct from oedema, which is important in assessing the effects of drugs such as thrombolytics which may encourage oedema formation while improving cerebral perfusion. MRI may also distinguish the ischaemic penumbra from the infarct core, as an area of peripheral hyperintensity (Ramadan et al, 1989). MRI frequently identifies brainstem infarcts which are either too small to be seen, or are 'hidden' because of bony artefact on CT (Weisberg et al, 1984).…”
Section: Introductionmentioning
confidence: 99%